Analysis of Language Errors in the Pronunciation of Chinese Polyphonic Letters - Lusi, Lusi; Thamrin, Lily (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Polyphonic letters are unique in learning Mandarin language because they have more than one pronunciation sound, so they quickly cause language errors. This research is a descriptive study that analyzes language errors at the level of Mandarin phonology made by final semester students in the Mandarin language education study program. The research aims to discover the forms of language errors and the factors that cause them. Research data was obtained using tests and interviews directly with Mandarin language students from the results of pronunciation tests and interviews with students. From the analysis of language errors, four types of errors were found, including pronunciation errors due to changes in tone, pronunciation errors due to changes in consonants, pronunciation errors due to changes in vowels, and pronunciation errors due to changes in vowels and consonants simultaneously. Of these four types of pronunciation errors, the one with the highest error rate is the pronunciation error due to changes in tone. Factors that cause pronunciation errors in polyphonic letters are the complexity of the pronunciation sounds of the polyphonic letters themselves and inadequate mastery of Mandarin language rules and vocabulary. In learning Mandarin, polyphonic letters are not explicitly discussed per letter but per vocabulary, so it depends on the student’s astuteness to remember the pronunciation sounds.